Research Status of Hydrocarbons as Refrigerants on Large and Medium-sized Commercial Equipment - Zhong Zhifeng; Hu Jiehao; Li Xiaoyan; Feng Hui; Wu Jianhua (Zhileng xuebao)
Hydrocarbons, whose environmental performance (ODP=0, GWP is extremely low) and thermophysical properties is excellent, can be selected as future alternative refrigerants. The research status of the application of HCs on large and medium-sized commercial equipment is introduced from aspects of commercial heat pumps, cascade system for supermarkets and other commercial equipment. Researches indicate that hydrocarbons behave well in the actual operation of the refrigeration system. Measures of reducing the refrigerant charge due to flammability, such as using micro-channel, plate heat exchanger, adopting indirect systems, are taken to make sure safe operation of refrigeration system.